Pendampingan Penyusunan Pembukuan Sederhana Bagi UMKM Toko Kelontong Asep Kecamatan Bekasi Utara - Idel Eprianto; Ery Teguh Prasetyo; Triana Yuniati; Tutiek Yoganingsih (Jurnal Abdimas Ekonomi dan Bisnis (JAmEB), 2022)
The purpose of this service activity is to overcome one of the problems that often occur by MSME business actors, namely regarding the management of bookkeeping in MSMEs which is realized through a simple bookkeeping assistance program. The method in this service is carried out through providing material about the introduction of simple bookkeeping, providing an understanding of how to compile simple bookkeeping and accompanying bookkeeping practices. The object of service is the Asep Grocery Store which is located at Marga Mulya Village, North Bekasi District.The results in this service activity found that so far the practice of simple bookkeeping in the Asep Grocery Store business was not continuous and not stored and there was no standard format. With this activity, it is hoped that business owners have an understanding of financial records and feel the benefits of the importance of bookkeeping. Suggestions for further service development can continue through the form of accounting and bookkeeping activities through information technology-based applications that are simple and easy to understand by the owner.